The Plasma Distribution of Non-cholesterol Sterol Precursors and Products of Cholesterol Synthesis and Phytosterols Depend on HDL Concentration - Nunes, Valéria Sutti; da Silva, Eliton Juniro; Ferreira, Guilherme da Silva; Assis, Sayonara Ivana Santos de; Cazita, Patrícia Miralda; Nakandakare, Edna Regina; Zago, Vanessa Helena de Souza; de Faria, Eliana Cotta; Quintão, Eder Carlos Rocha (Frontiers in Nutrition, 2022)
Non-cholesterol sterols are transported in plasma lipoproteins and are consequently important in cholesterol metabolism. We investigated the distribution of non-cholesterol sterol precursors of cholesterol synthesis (NCSPCS), oxysterols, and phytosterols in lipoproteins of healthy subjects differing according to HDL-Cholesterol (HDL-C) plasma levels. Elevated NCSPCS (desmosterol, lathosterol) in the High HDL group suggests that HDL exports these sterols from cells but not the cholesterol metabolite 24-OHC which was higher in the Low HDL group than in the High HDL group. 27-hydroxycholesterol (27OH-C) plasma levels did not differ between groups. Percentage of NCSPCS and phytosterols predominates in LDL, but did not differ between groups. 30% of desmosterol and lathosterol are present in HDL, with the High HDL group carrying higher percentage of these sterols. A high percentage of campesterol and sitosterol in HDL suggests that phytosterols are absorbed by enterocytes and that HDL could be a marker of the ABCA1/ApoA1 intestinal activity.